2019
DOI: 10.1111/jen.12621
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of selected apple cultivars to the Mediterranean fruit fly

Abstract: Ceratitis capitata (Wiedemann), the Mediterranean fruit fly, is one of the key pest species affecting deciduous fruit orchards along the Mediterranean coasts. Because of global warming, C. capitata is gradually spreading north and is becoming a major pest of apples. Determining the susceptibility of the main apple varieties grown in the region will serve as a cornerstone to the management of this pest. In this study, we show the results of a field and laboratory no‐choice test conducted to determine the Medfly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 54 publications
1
5
0
Order By: Relevance
“…In contrast with other studies (Li et al 2009; Szyniszewska and Tatem 2014) our model does not predict suitable habitats for the establishment of C. capitata in the UK, Ireland and in vast areas of northern France, Belgium, Netherlands and Poland. Our results seems more in line with current knowledge, attesting the northernmost presence of stable C. capitata populations in southern France, northern Italy and Austria (Cayol and Causse 1993;Rigamonti et al 2002;Rigamonti 2004Rigamonti , 2005Egartner et al 2017;Zanoni 2018;Zanoni et al 2019). Other results similar to our predictions are found in Vera et al (2002) and, limited to Italy, in Gutierrez and Ponti (2011).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In contrast with other studies (Li et al 2009; Szyniszewska and Tatem 2014) our model does not predict suitable habitats for the establishment of C. capitata in the UK, Ireland and in vast areas of northern France, Belgium, Netherlands and Poland. Our results seems more in line with current knowledge, attesting the northernmost presence of stable C. capitata populations in southern France, northern Italy and Austria (Cayol and Causse 1993;Rigamonti et al 2002;Rigamonti 2004Rigamonti , 2005Egartner et al 2017;Zanoni 2018;Zanoni et al 2019). Other results similar to our predictions are found in Vera et al (2002) and, limited to Italy, in Gutierrez and Ponti (2011).…”
Section: Discussionsupporting
confidence: 92%
“…However, Papadopoulos et al (1996Papadopoulos et al ( , 1998Papadopoulos et al ( , 2001 reported the capacity of the species to overwinter as larva in cold winter conditions and survive in subfreezing temperatures. Stable C. capitata populations have been reported in southern France (Cayol and Causse 1993), northern Italy (Rigamonti et al 2002;Rigamonti 2004Rigamonti , 2005Zanoni 2018; Zanoni et al 2019), and Austria (Egartner et al 2017) suggesting the capacity of the species to complete its life-cycle in areas far above its traditional northward distribution limit. Climate change is expected to play a primary role in altering the potential distribution and performance of the species worldwide (Gutierrez and Ponti 2011;Sultana et al 2020), and in the species' capacity to reinvade new areas by local transient populations (Lux 2018).…”
Section: Ecology Of Ceratitis Capitatamentioning
confidence: 99%
“…In addition, it is considered one of the most important quarantine pests with consequences for international fruit market due to quarantine restrictions (Rössler and Chen 1994; Malacrida et al 2007;Hulme 2009;Karsten et al 2015). Moreover, and because of climate change, the range of the med y activity has been expanding over the recent years in areas far beyond its traditional northward distribution limit (Lux 2018;Zanoni et al 2019;Sultana et al 2020;Gilioli et al 2022). The control of med y is based on a variety of tools ranging from pesticides (cover sprays and bait application), mass trapping, the Sterile Insect Technique (SIT) and the use of biological control, the latter involving both biological control agents and entomopathogens (Wharton 1989; Konstantopoulou and Mazomenos 2005; Argov and Gazit 2008; Beris et al 2013;Mokrini et al 2020;Bali et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Due to climate change, recent scenarios predict a northward expansion of the distribution area in Europe by 42% in 2050 compared to the 2020 presence data [ 4 ]. Current knowledge attests to stable populations further north in southern France and northern Italy [ 3 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%